Design and Construction of a Solar Concentrator System as a Small-Scale Electrical Energy Harvester - MUSAFA, AKHMAD; CHAN, HERLANGGA PRATAMA; AZZAHRA, CHEISA KURNIA; KHAIRUDIN, DICKY; FATH, NIFTY (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2025)
Harvesting solar energy as an alternative source of electrical energy, besides using photovoltaic panels, can also be done with a solar concentrator. This paper discusses the design of a solar concentrator system that uses a parabolic antenna as a small-scale electrical energy harvester. The inner surface of the parabola is coated with a metallized PET film, which is to reflect sunlight to a single focal point on an iron plate attached to a thermoelectric generator (TEG). The TEG functions to convert heat energy into electrical energy. The Peltier SP1848 output voltage will be increased using a boost converter to reach a voltage level that can be used for battery charging. The electrical energy stored in the battery is used to supply the AC power load. The experimental findings indicate that the electrical energy yield of the solar concentrator is 3.8 volts, with an average ambient temperature of 200C.